Analisis Determinan Inovasi dan Teknologi pada Pendapatan Usaha Mikro Kerupuk Ikan Di Kecamatan Pelayangan Kota Jambi - Rafidah Rafidah (Indonesian Journal of Islamic Economics and Business, 2019)
This paper aims to analyze the factors that influence the income of home industry fish crackers in district Pelayangan, the factors are technology and innovation. This research uses primary sources by distributing questionnaires to home industry owner, The sample used in this research were fish cracker home industry player in District Pelayangan Jambi city. The sampling technique was conducted using Stratified Random Sampling with total of 40 samples. The quantitative approach with multiple regression analysis is used to describe the determinant of each variable. The result shows that t hitung for innovation is 3,569 with significant value 0,001, while technology T hitung is 2,070 with significant value 0,045. Generally, all variable has adjusted R-value 0,35, its mean, innovation andtechnology have 35% effect to home industry income in district pelayangan, Jambi city.